Paciente de 57 años de sexo masculino con uveítis anterior hipertensiva. - Aguiar Daza, Melissa Fernanda (2021)
Anterior uveitis is a rare but very important pathology due to its consequences of not being treated in time and it leads to loss of vision and this causes the eyeball to have discomfort when viewing objects around it. In addition, this is how the vision is presented in a blurred way, which makes the images that are sent to the brain arrive incorrectly since the eye cannot correctly see the characteristics of the objects at the time of focusing on the patient. The method used in the treatment of anterior uveitis is more complicated due to the economic factor of the patients, some aspects such as age are taken into account, it is also considered in problems of the immune system. Diagnosing anterior uveitis in time to avoid serious consequences for the person who is suffering from it. The main objective of this clinical case is to establish the cause of poor vision in the right eye after the presence of the patient's anterior uveitis, fulfilling the tests required for comprehensive ophthalmological and optometric diagnoses, such as the assessment of visual acuity, tonometry, biomicroscopy and fundus. Among the results obtained through the study through the diagnostic tests of this clinical case, it was a moderate hypertensive anterior uveitis in the right eye of the patient, for which a constant check-up with an ophthalmologist and an optometrist is necessary, to comprehensive vision management.